Developing A Teaching Material Prototype for Linguistics Description of English Course - Hustarna Hustarna; Melati Melati (Universitas Jambi, Magister Program of English Education Department, 2019)
Linguistics Description of English is a new subject in the curriculum of English Education Study Program in the Faculty of Teacher Training and Education in Jambi University. Hence, the material for this subject is not yet available. Therefore, this research aims at developing a prototype of teaching materials for Linguistics Description of English course. By designing the prototype of teaching materials for this course, the researchers expected that lecturers who will teach this subject will not find difficulties in teaching this course. Besides, the use of materials which have been designed based on students’ need and linguistic lecturers’ discussion is anticipated to be able to encourage students to be more active in teaching and learning process. Thus, the choice of the topics is suited to the characteristics of the students and drew from the result of the need analysis questionnaire and forum group discussion (FGD) with the lecturers. This research utilized research and development design, based on the theory developed by Borg and Gall (1983). The result of the research is the prototype of the teaching materials for Linguistics Description of English course.